2010
DOI: 10.3233/ais-2010-0053
|View full text |Cite
|
Sign up to set email alerts
|

Multiagent system for joke generation: Humor and emotions combined in human-agent conversation

Abstract: In this paper we present an innovative work on a multiagent joking conversational system. In our research so far we have shown that implementing humor into a chatterbot can visibly improve its performance. The results presented in this paper are the outcome of the next step of our work. They show that a multiagent system, combining a conversational agent, a pun generator and an emotiveness analysis engine, works reasonably well in interactions with users. In the setup used in this research, the emotiveness ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…For example, in the field of natural language processing, numerous studies have attempted to estimate emotions and polarity (positive or negative) from conversations among people (e.g. [9,10]). These are a promising key technology.…”
Section: Quantification Of Ambiguities Of Facial Expressions and Contmentioning
confidence: 99%
“…For example, in the field of natural language processing, numerous studies have attempted to estimate emotions and polarity (positive or negative) from conversations among people (e.g. [9,10]). These are a promising key technology.…”
Section: Quantification Of Ambiguities Of Facial Expressions and Contmentioning
confidence: 99%
“…Also, in one of our earlier works [17] we proposed a humor-equipped chatterbot, able to generate simple puns during nonconstrained conversations with users. The evaluation experiments showed that most users assessed the system with humor as generally better, more interesting, and making them feel better than a similar system without humor.…”
Section: Processing Funniness-existing Work and Applicationsmentioning
confidence: 99%
“…Also results of an emotiveness analysis of chat logs showed that in most cases users' emotive states changed to more positive during and after conversations with the system with humor. For more details, see [17].…”
Section: Processing Funniness-existing Work and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations